Bibliometric analysis of 100 most cited articles on oral submucous fibrosis. (28th June 2018) - Gondivkar, Shailesh M.; Sarode, Sachin C.; Gadbail, Amol R.; Gondivkar, Rima S.; Chole, Revant; Sarode, Gargi S.
Abstract : Background: Citation analysis reflects the scientific recognition and influential performance of an article in the scientific community. The objective of this study was to identify and characterize the 100 most cited articles on oral submucous fibrosis (OSF). Methods: A list of 100 most cited articles related to OSF was retrieved from the Science Citation Index‐Expanded tool of Scopus database in May 2018. The articles were further reviewed, and basic information was recorded including the number of citations, citation density, journals, with its impact factor, category and quartile, publication year, authors, institution and country of origin, article type and level of evidence. Descriptive statistics were used to summarize the results. Results: The most frequently cited article received 780 citations, while the least frequently cited article received 49 (mean 107.5 citations per article). There were 38 different journals with Journal of Oral Pathology and Medicine having the most citations (n = 22). The 100 most cited articles were published from 1966 to 2013, with 81% published after 1990. Thirteen authors listed 5 or more articles in the top 100 list, and India was found to be the most prolific country with 38 articles. In terms of article type, there were 72 research articles and 28 review articles. Conclusions: This first citation analysis of the 100 most cited articles renders a historical perspective on the progress of research in the field of OSF and enables the comprehensive identification and recognition of the most important and relevant research topics concerned.